Association between electronic cigarette use in children and adolescents and coughing a systematic review. Issue 10 (18th August 2021) - Bourke, Michael; Sharif, Naseem; Narayan, Omendra
Abstract: Background: The use of electronic cigarettes (e‐cigarettes) among adolescents is increasing worldwide. E‐cigarettes are marketed as a safe alternative to other tobacco products. The aim of this systematic review is to evaluate whether e‐cigarette use in children and adolescents is associated with coughing. Method: Studies were identified through systematic searches of Excerpta Medica Database, Medline, Cumulative Index to Nursing and Allied Health Literature, British Nursing Index, OVID Emcare, Health Management Information Consortium, PsycINFO, and Allied and Complementary Medicine. The Grey Literature was also searched. Selected studies either contained only children and adolescents as study participants or if adults were included, the data for adolescents and children must be presented separately. Results: Seven studies were selected from 104. Three studies compared e‐cigarette users with nonusers; two studies found a significant association between coughing and e‐cigarette use in adolescence. Two studies investigated whether adolescents attributed their symptoms to their e‐cigarette use. One study reported that coughing was the most likely negative symptom reported by adolescents on initiation of e‐cigarette use; the other study found that adolescents, on initiation of e‐cigarette use, reported coughing. Two studies looked at the cases of children and adolescents who had presented to the hospital after e‐cigarette use and found coughing was a common presenting symptom. Conclusion: This systematic review shows that adolescent use of e‐cigarettes is associated with increased coughing and e‐cigarette users are more likely to report coughing compared to non‐users.